Topical Anti-Inflammatory Agents for Non-Infectious Uveitis: Current Treatment and Perspectives - Balasubramaniam B; Chong YJ; Azzopardi M; Logeswaran A; Denniston AK (Dove Medical Press, 2022)
Balini Balasubramaniam,1 Yu Jeat Chong,2 Matthew Azzopardi,3 Abison Logeswaran,4 Alastair K Denniston1 1Ophthalmology Department, Queen Elizabeth Hospital, University Hospitals Birmingham NHS Foundation Trust, Birmingham, B15 2TH, UK; 2Birmingham & Midland Eye Centre, Birmingham, B18 7QH, UK; 3Ophthalmology Department, Royal London Hospital, Barts Health NHS Trust, London, E1 1BB, UK; 4Moorfields Eye Hospital NHS Foundation Trust, London, UKCorrespondence: Yu Jeat Chong, Birmingham & Midland Eye Centre, Dudley Road, Birmingham, B18 7QH, UK, Email yu.chong.2@city.ac.ukAbstract: Non-infectious uveitis represents a heterogenous group of immune-mediated ocular diseases, which can be associated with underlying systemic disease. While the initial choice of treatment of non-infectious uveitis depends on a number of factors such as anatomical location and degree of inflammation, topical therapies often remain the initial choice of non-invasive therapy. In this narrative review, we aim to describe the literature on non-infectious uveitis, with specific focus on the current perspective on topical anti-inflammatory therapy.Keywords: non-infectious uveitis, topical anti-inflammatory therapy, topical corticosteroids, topical non-steroid anti-inflammatory drugs, topical cycloplegics